POLA PEMBINAAN ANAK DI PANTI ASUHAN (Studi pada Yayasan Rumah Yatim Arrohman Indonesia Jln. Sultan Agung No. 37 Kedaton, Bandar Lampung) - Purnomo, Dian; Rochana, Erna (SOCIOLOGIE, 2013)
The purpose of this research is to explain the pattern of Coaching Children in Orphanages Arrohman Indonesian. The methods used in this research is qualitative method. The technique of determining the informant with a purposive sampling technique, key informants in this study is the head of the branch, the head of the dormitory, builder and foster care. The process of collecting data with interviews, documentation, observation. Techniques of data analysis and data presentation, data reduction and withdrawal of the conclusion. The results of this research show that carried out a concerted pattern of authoritarian and democratic development that put more emphasis on Physical training, coaching, mentoring, coaching and Intellectual professions. Physical training is getting used to the child to follow the activities of sports such as gymnastics and healthy way in order to have a healthy and fit body. Construction of the religion that is the construction of the study about the system that regulates the faith (belief) and praying to the Almighty God and the rules relating to the guidelines for human beings and human beings and the environment. Construction of the intellect more leads to the childs academic ability meant that children can use in dealing with life issues intellect faced. Construction work and profession aims to provide economic security and youth labor candidates who are motivated, qualified ,skilled, creative and responsible.Keywords: Pattern, coaching